Implementasi Pengendalian Persediaan Dodol Dengan Metode Newsboy Problem Pada Toko Sejahtera Pasar Bengkel Serdang Bedagai - Farwansyah, Mhd Rio; Nasution, Hamidah; Lubis, Riri Syafitri (Proximal: Jurnal Penelitian Matematika dan Pendidikan Matematika, 2024)
Bengkel market is a souvenir or snack and is often referred to as a typical tour of Serdang Bedagai Regencey.Dodol with its flavor variant is the most famous product in this area, so it is often referred to as the DOdol Market. The prosperous shop has a problem, namely that there is often an excess of dodol production that does not sell well, thus making the store unable to optimize profits. The Newsboy Problem Method is a stochastic model that considers the existence of uncertainty factor in the amount of demand ffor each production period. From the results of research using the Newsboy Problem method, the optimal production quantity for the original lunkhead is 155 pcs with a profit of Rp.10.605.000. Pandan dodol produces an optimal production quantity of 110 pcs with a profit of Rp.10.920.000. and dodol durian produces an optimal production quantity of 125 pcs with a profit of Rp.9.990.000.